Patients with AML-MRC benefit from decitabine in combination with low-dose G-CSF, cytarabine and aclarubicin: A single center cohort study. (2022) - Liu, Jing; Liu, Xiaohong; Jia, Jinsong; Gong, Lizhong; Lu, Shengye; Wang, Jing; Huang, Xiao-jun; Jiang, Hao
Abstract: Patients with acute myeloid leukemia with myelodysplasia-related changes (AML-MRC) are insensitive to conventional chemotherapy and, therefore, have a poor prognosis. To evaluate the clinical efficacy and safety of low-dose decitabine in combination with small-dose CAG regimen (D-CAG regimen) in treating AML-MRC, a total of 80 patients with newly diagnosed AML-MRC from September 2015 to January 2020 in our center were included in the study. Amongst these patients, 43 and 37 patients received two courses of the D-CAG and CAG regimens, respectively. The complete remission (CR) and complete remission with incomplete blood count recovery (CRi) rate in the D-CAG group was higher than that of the CAG group (62.2% vs. 48.8%, P = 0.013). Among patients with less than 9 months of myelodysplastic syndrome (MDS) history and poor karyotypes, the (CR+CRi) rate of the D-CAG group was statistically higher than that of the CAG group. Except for patients receiving hematopoietic cell transplantation, among patients with less than 9 months of MDS history, the D-CAG group showed a better probability of overall survival than the CAG group did. In conclusion, patients with AML-MRC may benefit from the D-CAG regimen as an induction therapy, especially patients with less than 9 months of MDS history or with poor karyotypes.